Microfinance Services and Poverty Reduction in Sarawak, Malaysia - Solarin, Sakiru Adebola (International Journal of Economics and Financial Issues, 2021)
Despite the efforts of various federal and regional governments over the years, poverty still exists in several places across the world, especially in the developing countries. Microfinance services have been promoted as viable tools to decrease poverty. Sarawak, Malaysia is an example of a region where microfinance services are being used to reduce the incidences of poverty. This paper proposes a conceptual model to understand the effect of different microfinance services on poverty reduction efforts in Sarawak, Malaysia. This paper is further expanded into research hypotheses for subsequent papers on the nexus. The model will serve as a valuable guide for approaches on using microfinance services in reducing poverty. Keywords: Microfinance services; Poverty reduction; Sarawak; Malaysia JEL Classifications: G10; G20 DOI: https://doi.org/10.32479/ijefi.11258